Neighborhood History as a Factor Shaping Syringe Distribution Networks Among Drug Users at a U.S. Syringe Exchange1 - Braine, Naomi (2008)
Throughout the US, high-visibility drug markets are concentrated in neighborhoods with few economic opportunities, while drug buyers/users are widely dispersed. A study of Pittsburgh Syringe Exchange participants provides data on travel between and network linkages across neighborhoods with different levels of drug activity. There are distinct racial patterns to syringe distribution activity within networks and across neighborhoods. Pittsburgh’s history suggests these patterns emerge from historical patterns of social and economic development. Study data demonstrate the ability of IDUs to form long term social ties across racial and geographic boundaries and use them to reduce the risk of HIV transmission.